Desain Metode Fuzzy Untuk Pengendalian Kumbung Jamur Terintegrasi IoT - Mohammad Bhanu Setyawan; Angga Prasetyo (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2022)
The ideal conditions for growing oyster mushrooms are at 65-75% humidity and 29-31C during incubation, while the stem growth should be at 70-90% humidity and 29-32C. Thisideal ecosystem is maintained by aeration and manual watering, but the results have not beenmaximized in preventing damage to the mycelium during the incubation period which results indecreased crop yields. Automatic control has not been able to create ideal conditions becausethe procedure for regulating air temperature and humidity is only based on fans and sprayerswhich do not directly affect air conditions. Fuzzy logic used in industry to manage sensors,accuators, robotics can be combined with the Internet of Things to solve this problem. Theperformance of fuzzy logic in this system can be seen from the PWM response of the fan and theduration of the pump. The test results of this control device are able to manipulate temperature,humidity, in the oyster mushroom kumbung to create ideal conditions of 29 C-31 C, thus makingoptimal mushroom growth with an average daily harvest of 4 kg.